Handbook of gold exploration and evaluation - Macdonald, Eoin H. (Woodhead Publishing series in metals and surface engineering., 2007)
Designed for geologists and engineers engaged specifically in the search for gold deposits of all types and as a reference for academics in higher schools of learning, Handbook of gold exploration and evaluation provides principles and detailed explanations that underpin the correct interpretation of day-to-day experience in the field. Problems are addressed with regard to the analysis, interpretation and understanding of the general framework within which both primary and secondary gold resources are explored, developed and exploited. Handbook of gold exploration and evaluation covers a comprehensive range of topics including the nature and history of gold, geology of gold ore deposits, gold deposition in the weathering environment, sedimentation and detrital gold, gold exploration, lateritic and placer gold sampling, mine planning and practise for shallow deposits, metallurgical processes and design, and evaluation, risk and feasibility. Covers the nature and history of goldAddresses problems with regard to the framework in which gold resources are explored, developed and exploitedDiscusses topics including the geology of gold ore deposits, metallurgical processes and design, evaluation, risk and feasibility.